New species of Heteropterna Skuse and Keroplatus Bosc (Diptera: Keroplatidae) become the second records of this family for Cuba - Mederos, Jorge (Zootaxa, 2018)
Two new species of Keroplatini (Diptera: Keroplatidae: Keroplatinae), Heteropterna (Heteropterna) garae n. sp. and Keroplatus maxi n. sp. are described from Cuba, the second record of the family from this territory since Matile’s paper in 1977. Heteropterna garae n. sp. is characterized by the last three flagellomeres being a silvery white colour (the last with a light brown apical border), the wings with a distinct colour pattern, and the unique shape of the terminalia and gonostylus. Keroplatus maxi n. sp. is principally yellow with almost no marks except for the particular pattern of stripes on the dorsal part of thorax. The wings have a slight pale yellowish tint with no pattern of coloured spots, and the gonostylus is characteristically shaped. A key to Neotropical Heteropterna and Keroplatus species is provided.